Prevalence of Sarcopenic Obesity Using Different Definitions and the Relationship With Strength and Physical Performance in the Canadian Longitudinal Study of Aging - Purcell, Sarah A.; Mackenzie, Michelle; Barbosa-Silva, Thiago G.; Dionne, Isabelle J.; Ghosh, Sunita; Siervo, Mario; Ye, Ming; Prado, Carla M. (Frontiers in Physiology, 2021)
The occurrence of sarcopenic obesity and its relationship with physical performance parameters has not been described in the Canadian population. Therefore, the aim of the current investigation was to describe the prevalence of sarcopenic obesity using different published definitions and their relationship with handgrip strength and walking speed in older Canadian adults. Individuals aged 65+ in the Canadian Longitudinal Study on Aging (n=11,803; 49.6% male, 50.4% female) were included. Body composition was measured using dual X-ray absorptiometry (DXA). Sarcopenic obesity based on DXA was defined using 29 definitions. Low handgrip strength was identified as <27 kg in males and <16 kg in females and poor physical performance was defined as gait speed ≤8 m/s. The prevalence of sarcopenic obesity ranged from 0.1% to 85.3%in males, and from 0% to 80.4% in females. Sarcopenic obesity was frequently associated with low handgrip strength (p<0.05) in both males (14/17 definitions, 82.4%) and females (21/29 definitions, 72.4%). In very few definitions, sarcopenic obesity was associated with slow gait speed (males: 1/17 definitions [6.7%]; females: 2/29 [6.9%]). In conclusion, the prevalence of sarcopenic obesity varied greatly according to definitions and sarcopenic obesity was frequently associated with low handgrip strength.